Analisis Perhitungan Harga Pokok Produksi Dengan Menggunakan Metode Full Costing Dan Metode Variabel Costing Untuk Mengetahui Tingkat Laba Pada Groovy Cake Surabaya - Margareth Irawati; Revi Arfamaini (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Cost of production is all direct and indirect costs incurred by the company for the production process so that the goods or services can be sold. The aim of this research is to determine the determjination of the cost of production using the Full Costing and Variable methods. The data needed in this research includes sales data and costs that occurred during August 2022 for Groovy Cake as the object of this research. The type of data used is quantitative data which is primary data. Data collection methods are interviews with Groovy Cake leaders and documentation. Based on the research result, it can be seen that the result of calculating the cost of production using the full costing method is Rp.22.098.333. And the cost of production using the variable costing method is Rp.13.120.000. The operating profit obtained was Rp.18.056.667. The selling price is calculated using the cost plus pricing method with the full costing method with anb expected profit percentage of 65% and the variable costing method with different profit percentages. For 3 tier tarts the profit percentages is 68,5% and 1 tier tart 17%. Meanwhile, the sales profit percentage for 1 month using full costing and variable costing is 82% and 65%. After knowing these result, researchers found out the comparison between the two methods.